The investigation study using a questionnaire about the employment of Japanese breast cancer patients. (25th June 2018) - Kotani, Haruru; Kataoka, Ayumi; Sugino, Kayoko; Iwase, Madoka; Onishi, Sakura; Adachi, Yayoi; Gondo, Naomi; Yoshimura, Akiyo; Hattori, Masaya; Sawaki, Masataka; Iwata, Hiroji
Abstract : Our investigation study by a questionnaire about employment of Japanese breast cancer patients revealed the timing of quitting job and different employment state between patients in adjuvant and metastatic setting. Abstract: Background: Breast cancer is the most common cancer among women, and its survival rate has improved. As the number of cancer survivors increases, it is important to support their social comeback during and after treatment. Methods: Questionnaires were distributed to breast cancer patients treated in Aichi Cancer Center Hospital between June and November 2014. Responders were categorized according to adjuvant therapy (Group A: none, Group B: endocrine therapy, Group C: chemotherapy), or if they had advanced or recurrent breast cancer (Group D). Results: A total of 279 patients returned questionnaires (62, 79, 92 and 46 patients in Groups A, B, C and D, respectively). In adjuvant treatment groups, 43 patients (18.5%) quit their job during or after treatment. Most patients had quit their jobs at the time of diagnosis (7.5%), followed by those undergoing chemotherapy (5.6%) and those at the time of operation (4.9%). Quit rate from the workplace in which patients worked at the time of diagnosis was highest in Group C (30%), followed by Group B (20%) and Group A (13%). At the time of operation, 127 patients (57%) were absent from work. In Group D, 16 patients (35%) quit their job during treatment. Rates for patients currently working who had anxiety were 62, 30, 26 and 9% in Groups D, C, B and A, respectively. Conclusions: In adjuvant treatment groups, in which quit rate was highest at the time of diagnosis, consultation about working is necessary immediately after diagnosis. Patients treated most heavily had higher quit rates and experienced more anxiety about working.